(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
The Brazilian male beauty market occupies the second place in world consumption of cosmetics. Among the numerous products consumed by such audience is the capillary fixation mask, which is mainly composed by fixatives. These additives act on stabilizing the cosmetic emulsion, protecting the hair against moisture and also increasing the intensity of hair fixation. In this work, three formulations for modelling creams were prepared by different concentrations of the fixatives StylezeTM W20 and PVP K90 and their properties characterized by physicochemical, rheological and sensory analysis. The capillary masks produced were stable oil-in-water (O/W) emulsions with uniform droplets of 2.05- 2.82 μm sizes and pseudoplastic thixotropic behavior (0.19 < n < 0.26). It was possible to correlate the increased concentration of PVP K90 to a greater thixotropy and an improved yarn fixation, despite the worsening in the spreadability of the formulations. These results suggest properly conducted rheological measurements can contribute to the prediction of the emulsion’s sensory properties, which can save time and funds on the development of new cosmetics.